Joining sheet metals by electrically-assisted roll bonding. Issue 1 (2015) - Ng, Man-Kwan; Li, Lanyun; Fan, Zhaoyan; Gao, Robert X.; Smith, Edward F.; Ehmann, Kornel F.; Cao, Jian
Abstract Roll bonding is a solid-state welding process performed by means of rolling. During the process, virgin metal is extruded to the surface from underneath the surface through micro cracks leading to the formation of new metallic bonds. Electrically-assisted roll bonding (EARB) was applied to roll bond 127 μm aluminum sheet to 127 μm aluminum or copper sheets. The quality of the bonds was examined through micrographs and peel tests. It was found that the Joule heating effect in EARB lowered rolling forces and increased the bond strengths of bonded sheets by as much as three times.